Cancer and Thrombosis: New Treatments, New Challenges - Anders Erik Astrup Dahm (Medical Sciences, 2021)
The direct-acting oral anticoagulant (DOAC) has become an alternative to low-molecular-weight heparin (LMWH) for treatment and prophylaxis of venous thromboembolism (VTE) in cancer patients. The clinicians are, however, faced with difficult decisions regarding DOAC treatment: Which patients cannot use DOACs? Should incidental VTE be treated similar to symptomatic VTE? Is it safe to give DOACs to patients with gastrointestinal or urogenital cancers? How about drug–drug interactions? Should all cancer patients receive thromboprophylaxis? Is arterial thrombosis a problem? The current article reviews the available literature regarding these questions and aims to provide practical solutions based on data from the clinical trials and new guidelines.